2014
DOI: 10.12938/bmfh.33.11
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Some Lactic Acid Bacteria Isolated from Bee Pollen: A Preliminary Study

Abstract: In the present work, five hundred and sixty-seven isolates of lactic acid bacteria were recovered from raw bee pollen grains. All isolates were screened for their antagonistic activity against both Gram-positive and Gram-negative pathogenic bacteria. Neutralized supernatants of 54 lactic acid bacteria (LAB) cultures from 216 active isolates inhibited the growth of indicator bacteria. They were phenotypically characterized, based on the fermentation of 39 carbohydrates. Using the simple matching coefficient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Lactic acid bacteria are known to cause food spoilage such as milk fermentation (Zavisic et al, 2012). The growth of Gram-positive, facultative anaerobes such as Lactobacilli in the pollen samples of the current survey is similar with the findings of Belhadj et al (2014) who isolated Lactobacillus plantarum, L. fermentum, Lactococcus lactis, L. ingluviei, Pediococcus pentosaceus, L. acidipiscis, and Weissella cibaria from raw bee pollen grains collected in some Algerian areas.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Lactic acid bacteria are known to cause food spoilage such as milk fermentation (Zavisic et al, 2012). The growth of Gram-positive, facultative anaerobes such as Lactobacilli in the pollen samples of the current survey is similar with the findings of Belhadj et al (2014) who isolated Lactobacillus plantarum, L. fermentum, Lactococcus lactis, L. ingluviei, Pediococcus pentosaceus, L. acidipiscis, and Weissella cibaria from raw bee pollen grains collected in some Algerian areas.…”
Section: Discussionsupporting
confidence: 80%
“…In this context, humans may possibly be exposed to the negative influence of different fungal species, fungal spores, other invasive microorganisms or toxic fungal metabolites such as mycotoxins, directly by consumption of contaminated foodstuffs. Number of studies have revealed significant contamination levels of bee pollen by pathogenic microorganisms (Belhadj et al, 2014;Brindza et al, 2010), which compromise its safety for consumers. Bulgaria and other countries of the world, including Brazil, Poland, and Switzerland have established national standards for bee pollen (Campos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hill et al ( 2014 ), probiotics are defined as live microorganisms that when consumed in adequate amounts exert beneficial effects in the host with a GRAS status (Generally Regarded As Safe). Probiotic strains mainly include members of the genera Lactobacillus and Bifidobacterium , but bacteria belonging to the genus Pedioccocus have also been tested and already used (Vidhyasagar and Jeevaratnam, 2012 ; Martino et al, 2013 ; Belhadj et al, 2014 ; Savedboworn et al, 2014 ; Dubey et al, 2015 ; Chen et al, 2017 ). Such investigations have led to an obvious support of the significance of Pediococci in the field of probiotics, indicating that new isolated strains from various food matrices and belonging to this genus may play a key role to be used in new generation of functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…This may probably be due to the selected limited characters used for phenotypic study, or by the similarity of the metabolic patterns expressed by the isolates, due to similar nutritional requirements and growth under similar environmental conditions or by due to possible loss or acquisition of plasmids that encode many carbohydrate fermentation traits. As reported elsewhere (Belhadj et al, 2014), simple phenotypic tests used for a clear identification of LAB strain to species level are thus, often ambiguous. Therefore, 16S rDNA gene sequencing is used as molecular based characterization approach for discrimination and assignment of a given LAB strain to its taxonomic status (Soto et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Hierarchical cluster analysis grouped all the isolates into 18 different clusters at 78% similarity level. According to the fermentation profile, it seems that the isolates assimilated variously a panel of carbohydrates that reflected their enzymatic and genetic potentials (Belhadj et al, 2014). The LAB genomes are predicted to carry a large number of carbohydrate transport and utilization genes that display substantial variations among strains (Ceapa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%